The improvement of microclimate and soil characteristics in cocoa-tree agroforestry patterns - Ramces Sitohang; Eka Tarwaca Susila Putra; Cahyo Wulandari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2022)
Shade trees are used in agroforestry pattern for production and service aspects. Cocoa-tree agroforestry pattern is expected to improve atmospheric and rhizosphere zone in cacao plantations. However, the information related to this is still quite limited. This study was conducted using a nested design, with types of shade trees as nest. Shade trees used were Falcataria moluccana, Cocos nucifera, and Cassia spectabilis, and without shade was used as control. Variables observed were light, air temperature, humidity, soil temperature, soil texture, bulk density, permeability, and moisture content. Soil chemical properties were also observed, including organic C, pH, total N, P, K, Ca, Mg, B and content of available P, K, Ca, Mg, and B. The results showed that cacao agroforestry pattern using F. moluccana and C. spectabilis was able to improve the microclimate characteristics and soil fertility. However, F. moluccana showed lower soil fertility than C. spectabilis. F. moluccana and C. spectabilis shade trees were able to optimize light plants from 33 % to 34 %, and from 38 % to 39 %, respectively. F. moluccana could provide optimal air and soil temperature of 30 ⁰C to 32 ⁰C and 27 ⁰C, respectively. Meanwhile, C. spectabilis could provide optimal air and soil temperature of 29 ⁰C to 31⁰C and 26 ⁰C to 27 ⁰C, consecutively. Cocoa-tree agroforestry pattern using C. Spectabilis shade trees could optimize soil moisture content, pH, total N, and P, and availabilities of K, Ca, Mg, and B in soil.